Використання декодеру Вітербі в РНК блоках на ПЛІС - Кравцов, К. Р. (ХНУРЕ, 2020)
Convolutional and lattice codes are widely used in modern data transmission systems as noise-coding schemes. The popularity of these codes is due to the ability to decode them using the Viterbi algorithm.
Keywords: декодер Вітербі; ПЛІС; кодування